Universal access in human-computer interaction. 9th International Conference, UAHCI 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings /: 9th International Conference, UAHCI 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings. Access to learning, health and well-being : Part III, (2015) - Unknown
No abstract available